Habitat Preference of Auriscalpium vulgare Gray Inhabiting Slash and Burn Affected Khasi Pine Cones of India - Das, P.; Chettri, A.; Kayang, H. (Our Nature, 2010)
Slash and burn shifting cultivation or jhum is the predominant form of land use pattern in the hilly terain of northeast India. Impact of jhum practice on Auriscalpium vulgare growing on the female Khasi pine cone was studied. The period of mature cone falling proceeds after the slash and burn activity, hence only 1:3 escapes the burning practice. During the assessment, burned and unburned cones were assigned to coarse woody debris (CWD) and classified into three girth classes: small (≤10 cm), intermediate (>10 to ≤13 cm) and large (>13 cm). The mean number of basidiocarps in burned cones was significantly higher than unburned ones (p<0.00001). A significant linear relationship between girth size of burned cones and number of basidiocarps was observed (r = 0.736; p<0.01). The study reveals that maximum number of fungi thrives on the burned cones (anthropogenically disturbed) of pine and girth size affects the number of basidiocarp. Key words: burned and unburned pine cones; coarse woody debris (CWD); Khasi pine; slash and burn DOI: 10.3126/on.v7i1.2551 Our Nature (2009) 7:32-38